Species of Nepalomyia Hollis from Taiwan (Diptera: Dolichopodidae: Peloropeodinae) - Wang, Mengqing; Chen, Hongyin; Yang, Ding (Zootaxa, 2013)
An overview is presented for the species of the genus Nepalomyia Hollis, 1964 from Taiwan. Nepalomyia xiaoyanae sp. nov. is described and N. brevifurcata (Yang & Saigusa, 2001) and N. orientalis (Yang & Li, 1998) are recorded from Taiwan for the first time. A key is provided for all seven named species of this genus from Taiwan.